Dopamine‐Based Coatings and Hydrogels: Toward Substitution‐Related Structure–Property Relationships. Issue 24 (21st October 2014) - Cui, Jiaxi; Iturri, Jagoba; Paez, Julieta; Shafiq, Zahid; Serrano, Cristina; d'Ischia, Marco; del Campo, Aránzazu; Lendlein, Andreas; Behl, Marc
<x xml:space="preserve">Abstract</x> The influence of 6‐chloro and 6‐nitro substituents on the thickness, homogeneity, and general properties of coatings produced by controlled oxidative polymerization of dopamine and its β‐hydroxy derivative, norepinephrine, is investigated. Substitution at the catecholamine 6‐position affects the deposition kinetics due to modification of the oxidation potential of the catechol groups. Increasing the hydroxyl group acidity results likewise in changes in pH response and water uptake. A similar trend with pH is also observed in covalently crosslinked catechol‐functionalized PEG‐hydrogels, while an opposite behavior is measured in metal crosslinked films. These results pave the way toward the definition of structure–property relationships based on dopamine substitution effects in polycatecholamine layers and derived polymers. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>